Carcass percentage and quality of broilers given a ration containing probiotics and prebiotics - Daud, Muhammad; Piliang, Wiranda G; Kompiang, I. Putu (Indonesian Animal Sciences Society, 2007)
Probiotics is a feed additive in the form of life microorganisms that balance microorganism population in the digestive tract. While prebiotics is a feed substance which is not digested, and selectively improves growth and activity of useful microbes in large intestine. The objectives of this research were to study the carcass percentage and carcass quality of broilers given a ration containing probiotics and prebiotics. Four hundred eighty day-old chicks of broiler Arbor Acres strain were divided into four dietary treatments and three replications (40 birds / replicate). Ration used was consisted of: R1 = basal ration + 0.01% antibiotics (Zinc bacitracin), R2 = basal ration + 0.2% probiotics (Bacillus spp), R3 = basal ration + 0.2% probiotics + 0.5% prebiotics and R4 = basal ration + 0.5% prebiotics (katuk leaves). The variables observed were: carcass percentage, fat content in the abdomen, liver and carcass, cholesterol content in the liver, carcass and blood serum. The results showed that the carcass quality of broiler received probiotics and prebiotics either independently or the combination was significantly (P<0.05) different. The fat content of liver and thigh, and breast cholesterol of R3 was significantly (P<0.05) lower than that of the control (R1). It is concluded that combination of probiotics and prebiotics were able to decrease the carcass fat and cholesterol content at six week of age. Key Words: Probiotics, Prebiotics, Carcass, Broilers